Cadmium‐1, 3, 6, 8‐tetrakis(4‐carboxylphenyl)pyrene Framework as a Thermometer for Fluorescence Sensing of Temperature. Issue 24 (10th December 2019) - Zeng, Xue‐Yun; Liu, Rui; Liu, Dan‐Dan; Liu, Qing‐Yan; Wang, Yu‐Ling
Abstract : Compounds exhibiting tunable fluorescence emission upon adjusting the temperature are considered smart materials. Herein a three‐dimensional structure of [Cd(TBAPy)(H2 O)2 ]· 4(H2 O) n (1 ) constructed from Cd II and 1, 3, 6, 8‐tetrakis(4‐carboxylphenyl)pyrene (TBAPy 4– ) ligand was synthesized and characterized. Temperature‐dependent fluorescence studies showed the emission intensities for compound 1 decrease as temperature increasing. The emission intensity is linearly related to temperature in the range of 100 to 300 K. This findings demonstrate that compound 1 is a good candidate for temperature sensitive sensor over a wide temperature range. Such a fluorescence behavior is closely related to the highly conjugated organic ligand with a pyrene core. Abstract :